THE MECHANISM OF DEALING WITH OVERDUE AND BAD DEBTS (NON-PERFORMING LOANS)IN A RETAIL LOAN PORTFOLIO OF RUSSIAN BANKS - V. Mazurin (Вестник университета, 2016)
The article is about arrears in a retail credit portfolio of the Russian banks as one of the key indicators of its quality. An essence of the concepts "overdue" and "problem loan debt" (or a non-performing loan) are specified, the amount of these terms, borders of their application are denoted it the article. In particular positions of some leading financial institutions on the designated perspective are explained in this article. The main objective of this item consists in the description of the mechanism of the organization of high-quality work with arrears with an emphasis on a retail loans portfolio.